Augmented reality in neurosurgical navigation: A survey. Issue 6 (25th September 2020) - Liu, Tao; Tai, Yonghang; Zhao, Chengming; Wei, Lei; Zhang, Jun; Pan, Junjun; Shi, Junsheng
Abstract: Background: Neurosurgery has exceptionally high requirements for minimally invasive and safety. This survey attempts to analyse the practical application of AR in neurosurgical navigation. Also, this survey describes future trends in augmented reality neurosurgical navigation systems. Methods: In this survey, we searched related keywords 'augmented reality', 'virtual reality', 'neurosurgery', 'surgical simulation', 'brain tumour surgery', 'neurovascular surgery', 'temporal bone surgery' and 'spinal surgery' through Google Scholar, World Neurosurgery, PubMed and Science Direct. We collected 85 articles published over the past 5 years in areas related to this survey. Results: Detailed study has been conducted on the application of AR in neurosurgery and found that AR is constantly improving the overall efficiency of doctor training and treatment, which can help neurosurgeons learn and practice surgical procedures with zero risks. Conclusions: Neurosurgical navigation is essential in neurosurgery. Despite certain technical limitations, it is still a necessary tool for the pursuit of maximum security and minimal intrusiveness.